Nomenclatural notes on Trichanthecium (Poaceae, Panicoideae, Paniceae) - Lopes-Neto, Ray Balieiro; Zuloaga, Fernando Omar; Viana, Pedro Lage (Phytotaxa, 2025)
Trichanthecium is a genus of panicoid grasses that occurs in tropical and subtropical areas of the Americas, continental Africa and Madagascar, comprising 52 species. Revisions of herbaria materials revealed the need for new typifications of names associated with Trichanthecium to stabilize the nomenclature of the genus. In this article, we designate lectotypes for 16 names (three in Isachne and 13 in Panicum) within ten species of Trichanthecium: Panicum cyanescens var. rigidiusculum (Trichanthecium cyanescens), P. dinklagei (T. dinklagei), P. pusillum var. glabriglumatum (T. glaucocladum), P. homblei (T. margaritiferum), Isachne kidumaensis, I. wombaliensis and P. fulgens (T. nervatum), P. perpusillum (T. polycomum), P. carinifolium and P. praealtum (T. praealtum), P. cyanescens var. latifolium (T. schwackeanum), I. sapinii and P. strictissimum (T. strictissimum), and P. drosocarpum, P. gemmeum and P. viciniflorum (T. tenellum). We also indicate a new synonym under T. tenellum: P. imbelle. Typification notes and images of the type-specimens are presented.